O listach Jana Lechonia i Kazimierza Wierzyńskiego (Kilka uwag na marginesie przygotowania edycji krytycznej) - Dorosz, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
This article presents the problems faced by an editor preparing a correspondence dialogue between Jan Lechoń and Kazimierz Wierzyński (237 mainly handwritten letters from 1941-1956) for a critical edition, among others, the issue of completeness, dating, reading of the autograph. It signalizes some of the appearing motifs and problems in the letters, making an initial attempt to interpret them in the context of biographies of both authors and historical events (especially the experiences of emigration). Moreover, it contains seventeen short poetic pieces (poems, epigrams and trifles) by both poets which may be found among other contents on the pages of those letters. They have been read from the handwritten manuscripts and edited and therefore they appear in print for the very first time.
About Jan Lechoń’s and Kazimierz Wierzyński’s letters (A few remarks on the margin of the preparation of a critical edition)
Keywords: Wierzyński Kazimierz; Lechoń Jan; epistolografia - XX w.; edytorstwo; emigracja XX w.